Effects of lacidipine on peak oxygen consumption, neurohormones and invasive haemodynamics in patients with mild to moderate chronic heart failure. - de Vries, R. J. (1996)
OBJECTIVE: To evaluate the efficacy and safety of the second generation dihydropyridine calcium channel blocker lacidipine in patients with heart failure. DESIGN: Placebo controlled, parallel group, double blind study over 8 weeks. SETTING: General community hospital in Breda, The Netherlands. PATIENTS: A random sample was studied of 25 outpatients with symptoms of mild to moderate heart failure, despite treatment with diuretics, digoxin, and angiotensin converting enzyme inhibitors. Their mean age was 65 years, with mean left ventricular ejection fraction of 0.24 and a peak oxygen consumption of 14.4 ml/min/kg. Two patients dropped out on lacidipine, one patient on placebo. INTERVENTION: Treatment with lacidipine 4 mg once daily or placebo for eight weeks. MAIN OUTCOME MEASURE: Cardiopulmonary exercise testing, invasive haemodynamics, and plasma neurohormones. RESULTS: Treatment with lacidipine 4 mg once daily, as compared to placebo treatment, significantly improved peak oxygen consumption (P < 0.02), cardiac index (P < 0.01), and stroke volume (P < 0.03) paralleled by a decrease in systemic vascular resistance (P < 0.03) and arteriovenous oxygen content difference (P < 0.01). Plasma noradrenaline, plasma renin activity, and aldosterone values did not differ between lacidipine and placebo. CONCLUSIONS: This second generation dihydropyridine may be of value as an adjunct to standard treatment in congestive heart failure patients.